FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP TINGKAT KUNJUNGAN WISATAWAN KE OBYEK WISATA ALAM CURUG SEWU KABUPATEN KENDAL - , RIFKI IKHA KURNIASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kendal Regency is one of tourist destination in Central Java Province, who have several sites of natural objects such as ecotourism. One famous form of ecotourism in the Kendal regency is Natural Object of Tourism Curug Sewu waterfall. This study aims to determine the factors influenced to the tourist visits in Natural Object of Tourism Curug Sewu waterfall and to find tourist characteristics that support the factors influenced the level of tourist visits in the Natural Object of Tourism Curug Sewu waterfall. This study was conducted in August 2013 using survey methods and measuring instrument of questionnaires. Questionnaires conducted by random sampling with a sample of 90 respondents. Analysis was used to measure the socio-demographic and psychographic characteristics with quantitative descriptive analysis, to measure the factors influenced to the level of tourist visits using factor analysis with software SPSS 16.0 for Windows. Measurement of tourist characteristics that supported to the factors influenced the level of tourist visits were analyzed by crosstab analysis. The results found that formed the seven factors influenced the level of tourist visits to the Natural Object of Tourist Curug Sewu waterfall include (1) Tourist services, (2) Facilities traveled, (3) Accessibility (4) Cleanliness tourist sites, (5) The main means of travel, (6) Travel costs, (7) Value tourist attraction. Tourist characteristics that support the factors that most influenced the tourist visits is age 17 - 21 years with gender dominated by men, the majority of the work is the student/learner, education past high school / STM / MAN, the average income per month Rp2.500.000,00 - Rp5.000.000,00, the majority of the area of origin outside the Kendal area and the highest frequency of visits to the Natural Object of Tourism Curug Sewu waterfall performed once.